Changes in maximal power output and muscle torque for male volleyball players during a competitive season - Busko, K. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
Introduction: In volleyball technical and tactical skills, anthropometric characteristics and individual physical performance capacities are the most important factors that contribute to the competitive success of a whole team. Training for physical fitness in volleyball takes place primarily during the preparatory training period of the season, when less emphasis is directed to training of starting drills. During the competitive season the players concentrate mainly on technical and tactical skills, while the overall volume of training for physical fitness may be greatly reduced. The aim of the study was to examine the changes in maximal power output and maximal muscle torque for male volleyball players during the preparatory training period and the competitive season. Methods The study was conducted on six (6) volleyball players: age 25.0 5.3 years, body height 195.2 7.2 cm and body mass 91.2 14.7 kg. Maximal power output and maximal muscle torque measurements in static conditions were performed before the preparatory period (I), after the first competitive season (II) and after the second competitive season (III). Force-velocity and power-velocity curves were determined from five (5) maximal cycle ergometer exercise bouts, 10 s each, at increasing external loads equal to 2.5, 5.0, 7.5, 10.0 and 12.5% of body weight. The bouts were separated by 2 min rest periods. Maximal power output and the corresponding optimal velocity were computed from power-velocity curves. Maximal torque of the elbow, shoulder, knee, hip and trunk flexors and extensors were measured under isometric conditions on a special stand. The left and right limbs were measured and analysed separately. ANOVA/MANOVA procedures for repeated measures were used to analyse the data with post-hoc LSD test employed. Results Muscle torque for the right and left lower extremities increased insignificantly between the preparatory period (I) and the first competitive season (II) but decreased insignificantly during the second competitive season (III). Muscle torque for the right upper extremities increased (p<0.05) from 316.1±37.4 (I) to 341.7±32.0 N·m (II) and it decreased (p<0.05) during the second competitive season (315.9 ±22.2 N·m). Muscle torque for the left upper extremities increased (p<0.05) from 300.9±35.6 (I) to 328.6±44.5 (II) and 331.8±43.2 N·m (III). Muscle torque of the trunk increased significantly. No changes of the percent muscle topography of the sum of upper and lower extremities, and trunk were observed during the competitive season. Significant increases occurred in the maximal power output from 12.80±0.79 (I) to 13.11±0.94 (II) and 13.44±0.62 W·kg-1 (III). Discussion Volleyball has been described as an "interval" sport with both anaerobic and aerobic components, and volleyball players were classified as athletes specializing in power events. Thus the training of volleyball players should develop strength and power output. In this study training of volleyball players improved the muscle torque of the trunk, upper extremities and maximal power output, but the optimal velocity and the muscle torque of the lower extremities did not change significantly. In conclusion, the increases occurred in the maximal muscle torque of the right and left upper (significant), and lower (insignificant) extremities during the preparatory period and the first competitive season while decreases were observed during the second competitive season (with exception of the left upper extremities). The maximal power output increased during the competitive season..